An image-brightness amplifier based on copper bromide vapor for operation at increased superradiance pulse duration; Technical Physics Letters; Vol. 43, iss. 9 - Trigub M. V. Maksim Viktorovich; Vlasov V. V. Vasily Vasiljevich; Torgaev S. N. Stanislav Nikolaevich; Evtushenko G. S. Gennady Sergeevich (2017, 2017)
Title screen